Optimalisasi Peran Bank Wakaf dalam Keuangan Islam: Analisis Komparatif Implementasi dan Dampak di Indonesia, Malaysia dan Turki: Optimizing the Role of Waqf Banks in Islamic Finance: A Comparative Analysis of Implementation and Impact in Indonesia, Malaysia, and Turkey - Muhibuddin; Jaharuddin (Jurnal Bimas Islam, 2025)
This study examines the role of waqf banks in Islamic finance through a comparative analysis of their implementation and social impact in Indonesia, Malaysia, and Turkey. As an innovative instrument combining philanthropic principles with modern banking mechanisms, waqf banks are positioned to address gaps in social financing and support long-term socio-economic development. The findings reveal that Malaysia has successfully institutionalized waqf banks in funding social projects, such as scholarships and healthcare infrastructure, supported by comprehensive regulatory frameworks. In Turkey, waqf assets have been productively managed through formal financial channels, reflecting strong integration between traditional endowment models and contemporary asset management practices. Indonesia, meanwhile, is in a developmental phase, with various initiatives underway but still facing regulatory and institutional challenges. The study further highlights the potential of strategic collaboration between waqf banks and other Islamic financial institutions—such as Islamic banks and zakat agencies—to enhance liquidity, operational efficiency, and sustainability. By offering both conceptual insights and practical implications, this research contributes to a deeper understanding of waqf banking as a catalyst for inclusive development and proposes policy recommendations tailored to each national context.